What is 'antimicrobial resistance' and why should anyone make films about it? Using 'participatory video' to advocate for community-led change in public health. (1st March 2020) - Cooke, Paul; Shrestha, Ashim; Arjyal, Abriti; Giri, Romi; Jones, Nichola; King, Rebecca; Mitchell, Jessica; Tait, Caroline; Donlan, Inés Soria; Baral, Sushil
In this article, we discuss the role of participatory video (PV) as a tool for developing community-level solutions to 'Antimicrobial Resistance' (AMR) in Nepal. In recent years, PV has become an ever more popular tool in development contexts for supporting communities in low and middle income countries to raise awareness of issues that they do not feel are adequately represented in mainstream media. One area of growing interest in this regard is public health. However, PV has not, to date, been used to address AMR, currently considered to be one of the biggest public health issues we face globally. Placing our project within the wider context of 'participatory documentary' practice, we examine the world-view presented in the films this project generated, a dimension of such projects that is, somewhat curiously perhaps, often overlooked, with commentators tending to focus on the process of delivering PV, rather than the final products made. Here we are particularly interested in questions of power and how a close reading of the texts produced highlights the complexity of the power relationships at work in these films, which, in turn, can allow us to reflect in new ways on the processes at work in the project.